Peran Customer Relationship Management dalam Pengembangan Layanan Pelanggan di Industri E-Commerce: Studi Kasus Shopee Indonesia - Ahmad Al Fauzan; Egi Gufanda; Muhammad Nur Fahmi; Yoga Prawira Rukmana; Nurbaiti Nurbaiti (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the role of Customer Relationship Management (CRM) in developing customer service in the e‑commerce platform, specifically Shopee Indonesia. The research employs a descriptive qualitative method with data collected through in‑depth interviews with four active Shopee sellers from various regions, including Medan. The findings indicate that the implementation of CRM such as personalized communication, quick responses, customer incentives, and utilization of customer data significantly enhances customer satisfaction and loyalty. Shopee’s facilities and support, including Seller Centre Analytics, chat templates, and seller training, facilitate effective CRM implementation. The main challenges faced by sellers include high message volumes, limited digital literacy, and technical constraints, which can be addressed through adaptive strategies such as customer segmentation, chat templates, and admin team management. This study concludes that CRM is not merely a technical tool but a strategic approach for building long-term customer relationships, enhancing store reputation, and achieving business success in e-commerce.